Preparation method of quercetin nanocrystal enhanced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film

By combining quercetin nanocrystals with chitosan and polyvinyl alcohol, packaging films with enhanced mechanical properties and antioxidant properties were prepared, which solved the shortcomings of traditional packaging materials in extending the shelf life of fresh livestock and poultry meat and monitoring their safety and quality, and achieved effective antibacterial preservation and freshness indications.

CN119775607APending Publication Date: 2025-04-08SUNRISE PACKAGING MATERIAL (JIANGYIN) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963630.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional food packaging materials have shortcomings in extending the shelf life of fresh livestock and poultry meat and monitoring their safety and quality, and their biocompatibility and environmental friendliness need to be improved.

Method used

By combining quercetin nanocrystals with chitosan and polyvinyl alcohol, the covers were prepared by ultrasonic assisted cold crystallization, and a packaging film with enhanced mechanical properties and antioxidant properties was prepared by casting.

Benefits of technology

It significantly improves the mechanical properties and antioxidant properties of the packaging film, so that it can effectively inhibit the spoilage of fresh meat, extend the shelf life, and has the function of indicating freshness, reducing agricultural product waste and ensuring food safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775607A_ABST
    Figure CN119775607A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a quercetin nanocrystal enhanced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film, and relates to the technical field of agricultural product and food packaging. Quercetin crystals are prepared through an ultrasonic-assisted cold crystallization method, the quercetin crystals, chitosan and wheat protein peptide form a coating body, then the coating body serves as a functional material to be filled into a mixed film forming raw material of chitosan and polyvinyl alcohol, and the packaging material with enhanced mechanical performance and oxidation resistance is prepared through a tape casting method. The prepared antibacterial and fresh-keeping degradable packaging film for the raw fresh meat has the function of indicating the freshness of the fresh livestock and poultry meat, can be applied to the field of packaging and fresh keeping of agricultural products such as chilled meat, and has important significance on reducing waste of the agricultural products such as the fresh livestock and poultry meat and guaranteeing the safety of the agricultural products such as the fresh livestock and poultry meat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of agricultural products and food packaging, in particular to a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film and a preparation method thereof. Background Art

[0002] Fresh agricultural products such as fresh livestock and poultry meat are prone to spoilage during processing, storage, transportation and sales, and adverse reactions such as lipid oxidation and protein degradation occur, resulting in quality deterioration, which in turn causes waste and brings about food safety problems. People are in urgent need of advanced technical means to extend the shelf life of fresh livestock and poultry meat and monitor the safety and quality of fresh meat. The safety and functionality of food packaging materials are increasingly becoming the focus of global attention. Traditional food packaging materials have many problems, such as poor biocompatibility, environmental unfriendliness, and single function, which seriously restrict the high-quality development of the food packaging industry. With consumers paying more and more attention to food safety and green environmental protection, the development of new multifunctional, environmentally friendly, and intelligent food packaging materials has become an important direction of food packaging scientific research.

[0003] Chitosan and polyvinyl alcohol are bio-based materials for packaging that have attracted much attention due to their good film-forming properties, biocompatibility and biodegradability. However, their mechanical properties and functionality (antioxidant properties, antibacterial properties) still need to be improved. Quercetin is a plant polyphenol with a flavonol structure that is widely found in fruits and vegetables. It has strong physiological activity and can be used as an antioxidant active substance to develop active packaging. However, since quercetin is insoluble in water, direct incorporation into water-soluble bio-based materials will form large particles, destroying the continuity and density of the polymer chains of the bio-based materials, resulting in a decrease in the mechanical properties and barrier properties of the composite film. By introducing quercetin with improved water solubility into the chitosan / polyvinyl alcohol system, it is expected to significantly improve the mechanical properties and antioxidant properties of the composite film. Summary of the invention

[0004] The object of the present invention is to provide a quercetin nanocrystal reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film, comprising the following preparation steps:

[0006] (1) dissolving quercetin in anhydrous ethanol to obtain a quercetin-ethanol solution;

[0007] (2) adding the quercetin-ethanol solution dropwise into supercooled water with a volume 9 times that of the quercetin-ethanol solution, and simultaneously performing ultrasonic treatment to obtain a quercetin suspension solution;

[0008] (3) wheat gluten and deionized water were mixed and ultrasonically treated. The pH of the solution was adjusted to 8 with a 5 wt % sodium hydroxide aqueous solution. Trypsin was added and enzymatically hydrolyzed at 30-50° C. for 3 h, and then the enzyme was inactivated at 95° C. for 10 min. The mixture was centrifuged at a speed of 10,000 rpm for 8-20 min, and the supernatant was taken and dried at -48° C. for 20 h to obtain intermediate A.

[0009] (4) Mixing the intermediate A with deionized water, adjusting the solution pH to 11 with a 5 wt % sodium hydroxide aqueous solution, adding the quercetin suspension solution and the chitosan solution in sequence while stirring at 20 to 60 rpm, adjusting the solution pH to 6 with dilute hydrochloric acid, stirring at 200 rpm for 3 to 10 min, and then performing ultrasonic treatment to obtain a coating suspension solution;

[0010] (5) dissolving polyvinyl alcohol powder in deionized water at a dissolution temperature of 85 to 90° C. for 2 to 4 hours to obtain a polyvinyl alcohol solution having a concentration of 2 to 5 wt %; mixing the chitosan solution and the polyvinyl alcohol solution evenly, adding glycerol and the coating suspension solution, and then pouring the mixture into a mold, casting the mixture, and drying the mixture at 40 to 60° C. for 3 to 5 hours to obtain a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant biodegradable packaging film having a thickness of 0.01 to 0.03 mm.

[0011] Furthermore, the concentration of the quercetin-ethanol solution in step (1) is 10 to 30 mg / mL.

[0012] Furthermore, the ultrasonic parameters in step (2) are: frequency of 21 kHz and time of 10 to 20 min.

[0013] Furthermore, the concentration of the quercetin suspension solution in step (2) is 1 to 3 mg / mL.

[0014] Furthermore, the ultrasonic parameters in step (3) are as follows: temperature of 40 to 70° C., frequency of 60 Hz, and time of 10 to 30 min.

[0015] Furthermore, in step (3), the mass ratio of wheat gluten, deionized water and trypsin is 10:90:4.

[0016] Furthermore, in step (4), the mass ratio of the intermediate A, deionized water, quercetin suspension solution, and chitosan solution is 1:20:2:20.

[0017] Furthermore, the ultrasonic parameters of step (4) are: frequency of 30-50 kHz, intermittent ratio of 20 / 5s / s, power of 300W, and time of 5-13min.

[0018] Furthermore, the preparation method of the chitosan solution in step (4) and step (5) is as follows: dissolving chitosan powder in 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 50-60° C. for a dissolution time of 2-4 hours to obtain a chitosan solution having a concentration of 1.5-4wt%.

[0019] Furthermore, in step (5), the mass ratio of the chitosan solution, the polyvinyl alcohol solution, the glycerol, and the coating suspension solution is 10:5-30:0.045:1-3.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The present invention prepares quercetin crystals by ultrasound-assisted cold crystallization, forms a coating with chitosan and wheat protein peptide, and then fills the quercetin crystals into a mixed film-forming raw material of chitosan and polyvinyl alcohol as a functional material, and uses a casting method to prepare a packaging material with enhanced mechanical properties and antioxidant properties. The fresh meat antibacterial and fresh-keeping degradable packaging film prepared by the present invention has the function of indicating the freshness of fresh livestock and poultry meat, can be applied to the field of packaging and preservation of agricultural products such as chilled fresh meat, and is of great significance to reducing the waste of agricultural products such as fresh livestock and poultry meat and ensuring the safety of agricultural products such as fresh livestock and poultry meat.

[0022] The invention uses wheat gluten powder as a substrate, utilizes ultrasound pretreatment and trypsin enzymatic hydrolysis to obtain an active polypeptide structure, and hydrolyzes the substrate from the nitrogen-terminal polar space by trypsin to form a peptide containing clustered phosphoserine residues, and the ultrasound treatment can greatly enhance the emulsification stability of the polypeptide, which is conducive to the diffusion of the wheat protein peptide to the oil-water interface to achieve equilibrium, and then the quercetin crystal is coated with chitosan to enhance the stability of the quercetin structure and its dispersibility in the matrix, wherein the wheat protein peptide and the quercetin form a negatively charged substance through hydrophobic interaction, and then bridge with the chitosan molecular aggregate with a positive charge to form nanoparticles, and the particle size is increased, thereby loading more quercetin, and the cavitation effect generated by ultrasound is used again to increase the possibility of collision between molecules, so that the quercetin is more easily migrated to the inside of the polypeptide-polysaccharide complex, thereby improving the coating effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 This is a microstructure diagram of the quercetin nanocrystals prepared in the present invention.

[0025] Figure 2 This is a diagram showing the antibacterial effect of the quercetin nanocrystals prepared in the present invention on the dominant spoilage bacteria in fresh meat.

[0026] Figure 3 This is an analysis diagram of the scavenging effect of quercetin nanocrystals prepared in the present invention on DPPH and ABTS free radicals.

[0027] Figure 4 This is an analysis diagram of the optical and fluorescent color changes of the quercetin nanocrystals prepared in the present invention at different pH values.

[0028] Figure 5 This is a diagram showing the mechanical properties of the antioxidant bio-based degradable packaging film prepared in accordance with an embodiment of the present invention.

[0029] Figure 6 This is a water vapor barrier performance analysis chart of the antioxidant bio-based degradable packaging film prepared in an embodiment of the present invention.

[0030] Figure 7 This is a sensitivity analysis chart of the antioxidant bio-based degradable packaging film prepared in an embodiment of the present invention to volatile ammonia.

[0031] Figure 8 This is a diagram showing the degradation of the antioxidant bio-based degradable packaging film according to an embodiment of the present invention in soil. DETAILED DESCRIPTION

[0032] In order to make the features and advantages of the present invention more obvious, the present invention is further described in detail below in conjunction with the embodiments of the specification so that those skilled in the art can implement it according to the description.

[0033] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.

[0034] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the present invention can also be implemented in other ways; the reagents and materials described in the following embodiments can be obtained from commercial channels unless otherwise specified.

[0035] The main chemical reagents involved in the present invention: quercetin (CAS#117-39-5), purchased from Shanghai Yuanye Biotechnology Co., Ltd.; chitosan (CAS#9012-76-4, deacetylation degree>90%, viscosity 0.2pas), polyvinyl alcohol (CAS#9002-89-5, 1799 type), glycerol were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0036] Example 1

[0037] (1) dissolving quercetin in anhydrous ethanol to obtain a quercetin-ethanol solution having a concentration of 10 mg / mL;

[0038] (2) adding the quercetin-ethanol solution dropwise into supercooled water with a volume 9 times that of the quercetin-ethanol solution, and simultaneously performing ultrasonic treatment, wherein the parameters are: frequency of 21 kHz, time of 10 min, to obtain a quercetin suspension solution with a concentration of 1 mg / mL;

[0039] (3) Wheat gluten and deionized water were mixed and subjected to ultrasonic treatment at the following parameters: temperature of 40° C., frequency of 60 Hz, and time of 10 min. The pH value of the solution was adjusted to 8 with a 5 wt % sodium hydroxide aqueous solution. Trypsin was added and hydrolyzed at 30° C. for 3 h, and then the enzyme was inactivated at 95° C. for 10 min. The mixture was centrifuged at a speed of 10,000 rpm for 8 min, and the supernatant was taken and dried at -48° C. for 20 h to obtain intermediate A. The mass ratio of wheat gluten, deionized water, and trypsin was 10:90:4.

[0040] (4) Dissolving chitosan powder in 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 50° C. for 2 h to obtain a chitosan solution having a concentration of 1.5 wt %; mixing intermediate A with deionized water, adjusting the solution pH to 11 with a 5 wt % sodium hydroxide aqueous solution, adding quercetin suspension solution and chitosan solution in sequence while stirring at 20 rpm, adjusting the solution pH to 6 with dilute hydrochloric acid, stirring at 200 rpm for 3 min, and then performing ultrasonic treatment with the following parameters: frequency of 30 kHz, intermittent ratio of 20 / 5 s / s, power of 300 W, and time of 5 min to obtain a coating suspension solution; the mass ratio of intermediate A, deionized water, quercetin suspension solution, and chitosan solution is 1:20:2:20;

[0041] (5) The chitosan powder was dissolved in a 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 50°C for a dissolution time of 2 h to obtain a chitosan solution with a concentration of 1.5 wt%; the polyvinyl alcohol powder was dissolved in deionized water at a dissolution temperature of 85°C for a dissolution time of 2 h to obtain a polyvinyl alcohol solution with a concentration of 2 wt%; the chitosan solution and the polyvinyl alcohol solution were mixed evenly, glycerol and the coating suspension solution were added, and then poured into a mold, cast, and dried at 40°C for 3 h to obtain a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film with a thickness of 0.01 mm, denoted as PC@QNs1; the mass ratio of the chitosan solution, polyvinyl alcohol solution, glycerol, and coating suspension solution was 10:5:0.045:1.

[0042] Example 2

[0043] (1) dissolving quercetin in anhydrous ethanol to obtain a quercetin-ethanol solution having a concentration of 20 mg / mL;

[0044] (2) adding the quercetin-ethanol solution dropwise into supercooled water with a volume 9 times that of the quercetin-ethanol solution, and simultaneously performing ultrasonic treatment, wherein the parameters are: frequency of 21 kHz, time of 15 min, to obtain a quercetin suspension solution with a concentration of 2 mg / mL;

[0045] (3) Wheat gluten and deionized water were mixed and subjected to ultrasonic treatment at the following parameters: temperature of 50° C., frequency of 60 Hz, and time of 20 min. The pH value of the solution was adjusted to 8 with a 5 wt % sodium hydroxide aqueous solution. Trypsin was added and hydrolyzed at 40° C. for 3 h, and then the enzyme was inactivated at 95° C. for 10 min. The mixture was centrifuged at a speed of 10,000 rpm for 13 min, and the supernatant was taken and dried at -48° C. for 20 h to obtain intermediate A. The mass ratio of wheat gluten, deionized water, and trypsin was 10:90:4.

[0046] (4) Dissolving chitosan powder in 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 55° C. for 3 h to obtain a chitosan solution having a concentration of 2 wt %; mixing intermediate A with deionized water, adjusting the solution pH to 11 with a 5 wt % sodium hydroxide aqueous solution, adding quercetin suspension solution and chitosan solution in sequence while stirring at 40 rpm, adjusting the solution pH to 6 with dilute hydrochloric acid, stirring at 200 rpm for 7 min, and then performing ultrasonic treatment with the following parameters: frequency of 40 kHz, intermittent ratio of 20 / 5 s / s, power of 300 W, and time of 9 min to obtain a coating suspension solution; the mass ratio of intermediate A, deionized water, quercetin suspension solution, and chitosan solution is 1:20:2:20;

[0047] (5) The chitosan powder was dissolved in a 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 55°C for 3 hours to obtain a chitosan solution with a concentration of 2wt%; the polyvinyl alcohol powder was dissolved in deionized water at a dissolution temperature of 87°C for 3 hours to obtain a polyvinyl alcohol solution with a concentration of 3wt%; the chitosan solution and the polyvinyl alcohol solution were mixed evenly, glycerol and the coating suspension solution were added, and then poured into a mold, cast, and dried at 50°C for 4 hours to obtain a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film with a thickness of 0.02 mm, denoted as PC@QNs2; the mass ratio of the chitosan solution, polyvinyl alcohol solution, glycerol, and coating suspension solution was 10:20:0.045:2.

[0048] Example 3

[0049] (1) dissolving quercetin in anhydrous ethanol to obtain a quercetin-ethanol solution having a concentration of 30 mg / mL;

[0050] (2) adding the quercetin-ethanol solution dropwise into supercooled water with a volume 9 times that of the quercetin-ethanol solution, and simultaneously performing ultrasonic treatment, wherein the parameters are: frequency of 21 kHz, time of 20 min, to obtain a quercetin suspension solution with a concentration of 3 mg / mL;

[0051] (3) Wheat gluten and deionized water were mixed and subjected to ultrasonic treatment at the following parameters: temperature of 70° C., frequency of 60 Hz, and time of 30 min. The pH value of the solution was adjusted to 8 with a 5 wt % sodium hydroxide aqueous solution. Trypsin was added and hydrolyzed at 50° C. for 3 h, and then the enzyme was inactivated at 95° C. for 10 min. The mixture was centrifuged at a speed of 10,000 rpm for 20 min, and the supernatant was taken and dried at -48° C. for 20 h to obtain intermediate A. The mass ratio of wheat gluten, deionized water, and trypsin was 10:90:4.

[0052] (4) Dissolving chitosan powder in 2% (v / v) acetic acid aqueous solution at 60°C for 4 hours to obtain a chitosan solution having a concentration of 4 wt%; mixing intermediate A with deionized water, adjusting the solution pH to 11 with 5 wt% sodium hydroxide aqueous solution, adding quercetin suspension solution and chitosan solution in sequence while stirring at 60 rpm, adjusting the solution pH to 6 with dilute hydrochloric acid, stirring at 200 rpm for 10 minutes, and then performing ultrasonic treatment with the following parameters: frequency of 50 kHz, intermittent ratio of 20 / 5 s / s, power of 300 W, and time of 13 minutes to obtain a coating suspension solution; the mass ratio of intermediate A, deionized water, quercetin suspension solution, and chitosan solution is 1:20:2:20;

[0053] (5) The chitosan powder was dissolved in a 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 60°C for 4 hours to obtain a chitosan solution with a concentration of 4wt%; the polyvinyl alcohol powder was dissolved in deionized water at a dissolution temperature of 90°C for 4 hours to obtain a polyvinyl alcohol solution with a concentration of 5wt%; the chitosan solution and the polyvinyl alcohol solution were evenly mixed, glycerol and the coating suspension solution were added, and then poured into a mold, cast, and dried at 60°C for 5 hours to obtain a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film with a thickness of 0.03 mm, denoted as PC@QNs3; the mass ratio of the chitosan solution, polyvinyl alcohol solution, glycerol, and coating suspension solution was 10:30:0.045:3.

[0054] Comparative Example

[0055] The difference between the comparative example and embodiment 2 is that the comparative example does not have step (1), step (2), step (3) and step (4), and step (5) is changed to: dissolving chitosan powder in 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 55° C. and a dissolution time of 3 h to obtain a chitosan solution with a concentration of 2wt%; dissolving polyvinyl alcohol powder in deionized water at a dissolution temperature of 87° C. and a dissolution time of 3 h to obtain a polyvinyl alcohol solution with a concentration of 3wt%; mixing the chitosan solution and the polyvinyl alcohol solution uniformly, adding glycerol, and then pouring into a mold, casting, and drying at 50° C. for 4 h to obtain a chitosan / polyvinyl alcohol packaging film with a thickness of 0.02 mm, recorded as PC; the mass ratio of the chitosan solution, the polyvinyl alcohol solution, and the glycerol is 10:20:0.045; and the remaining steps are the same as in embodiment 2.

[0056] The performance was determined as follows:

[0057] (1) Microstructure of quercetin nanocrystals: The microstructure of quercetin nanocrystals was observed using scanning electron microscopy (SEM, SU 1510, Hitachi, Japan) and transmission electron microscopy (TEM, H-7500, Hitachi, Japan). Figure 1 ). Scanning electron microscopy and transmission electron microscopy images showed that quercetin nanocrystals were dispersed rod-shaped, and the crystal size decreased with the increase of ultrasonication time.

[0058] (2) Inhibitory effect of quercetin nanocrystals on dominant spoilage bacteria in fresh meat: Pseudomonas paralactis MN10, Acinetobacter pullicarnis MN21, and Lactobacillus sakei VMR17 were selected to test the antibacterial ability of quercetin nanocrystals (see Appendix). Figure 2 ), and the strains were provided by the Meat Science and Nutrition Engineering Innovation Team of the Institute of Agricultural Product Processing, Chinese Academy of Agricultural Sciences. Take 100μL of quercetin nanocrystal suspension, add 1mL of spoilage bacteria suspension (about 10^6CFU / mL) and mix, then incubate at 30℃ for 6h; then take 100μL of the mixed solution and spread it on LB solid culture medium, incubate in a 30℃ incubator for 12h and take photos. Quercetin nanocrystals have good antibacterial effects on fresh meat spoilage bacteria Pseudomonas MN10, Acinetobacter MN21 and Lactobacillus VMR17. It is worth noting that compared with original quercetin, quercetin nanocrystals have stronger inhibitory ability against these three spoilage bacteria. This may be because ultrasound-assisted low-temperature crystallization increases the solubility of quercetin nanocrystals in the aqueous phase system and is more easily dynamically absorbed by bacterial cell membranes.

[0059] (3) Antioxidant effect of quercetin nanocrystals: The antioxidant effect of quercetin nanocrystals was evaluated by DPPH and ABTS free radical scavenging experiments. The scavenging rates of quercetin nanocrystals on DPPH and ABTS free radicals were greater than 90% (see Appendix Figure 3 ), indicating that the phenolic hydroxyl structure of quercetin was not destroyed during the crystallization process of quercetin to form nanocrystals, and a strong free radical scavenging ability was retained.

[0060] (4) Optical and fluorescent color changes of quercetin nanocrystals at different pH values: The quercetin nanocrystal suspension was adjusted to a series of pH values, and the color changes of the quercetin nanocrystal suspension at different pH values ​​and the fluorescent color changes at an excitation wavelength of 365 nm were recorded (see Appendix Figure 4 ). The original quercetin has poor solubility in aqueous solution. After crystallization, the solubility of quercetin nanocrystals in aqueous solution is enhanced. The color difference of quercetin nanocrystal suspension at different pH values ​​can be observed by naked eyes, and the difference in fluorescent color is more obvious. This shows that quercetin nanocrystals can be used as a pH indicator to indicate freshness.

[0061] (5) Mechanical property measurement: The mechanical properties of the antioxidant bio-based degradable packaging films prepared in Examples 1 to 3 were measured using a texture analyzer (TA-XTPlus, Stable, UK), including tensile strength and elongation at break. Before the test, the example samples were cut into 10 mm × 60 mm rectangles, and 5 points were randomly selected to measure the thickness of the example, and the average value was used for subsequent calculations; during the measurement, the initial gap distance of the fixture was 30 mm, and the test speed was 50 mm / min. The measurement results are as follows: Figure 5 As shown in the figure, it can be seen that with the increase in the amount of quercetin nanocrystals added, the tensile strength of the antioxidant bio-based degradable packaging film shows a trend of first decreasing and then increasing. This is mainly because quercetin nanocrystals are a two-dimensional material that can entangle with chitosan / polyvinyl alcohol molecular chains through hydrogen bonding, which is manifested as an increase in tensile strength, while the flexibility and deformability of the composite film decrease. Compared with quercetin molecules, quercetin nanocrystals have a rod-like fiber structure and a high aspect ratio, which can form a uniformly dispersed filler in the chitosan / polyvinyl alcohol polymer chain, hinder the slippage of the polymer chain, increase the degree of entanglement between molecular chains, and increase the interaction between polymer molecular chains. At the same time, quercetin nanocrystals can form a hydrogen bond network with polymer chains through hydrogen bonds, which improves the integrity of the internal structure. Therefore, quercetin nanocrystals improve the mechanical properties of chitosan / polyvinyl alcohol composite films.

[0062] (6) Determination of water vapor barrier performance: The water vapor barrier performance of the antioxidant bio-based degradable packaging films prepared in Examples 1 to 3 was determined using the differential method; the sample of the example was fixed to the mouth of a 50 mL centrifuge tube with an opening diameter of 26.5 mm, and 20.0 ± 0.5 g of anhydrous silica gel was placed in each centrifuge tube. The mass change of the centrifuge tube was continuously recorded at 75% relative humidity and 25°C until the 7th day. The water vapor transmission rate (WVP) was calculated as follows:

[0063]

[0064] Wherein, Δm is the weight difference (g) of the centrifuge tube filled with anhydrous silica gel during the measurement, e is the thickness of the sealing example sample used (mm), t is the measurement time (s), A is the area of ​​the centrifuge tube mouth, and Δp is the pressure at 75% relative humidity.

[0065] The results of the test are as follows Figure 6 As shown in the figure, it can be seen that with the increase in the amount of quercetin nanocrystals added, the water vapor permeability of the composite film decreases, that is, the water vapor barrier capacity is enhanced. This may be because quercetin nanocrystals increase the tortuosity of the path for water molecules to pass through the membrane.

[0066] (6) Antioxidant performance determination: 95% ethanol solution and PBS solution were used as high-fat food and high-water food simulation systems, respectively, and ABTS and DPPH free radical scavenging experiments were performed to evaluate the antioxidant activities of Examples 1 to 3 and the comparative example in different food systems. The results are shown in Table 1. The scavenging effect of the antioxidant bio-based degradable packaging film on ABTS and DPPH free radicals was dose-dependent. In Example 3, the scavenging rates of the composite film on ABTS and DPPH free radicals in the high-fat food simulation system reached 94.61% and 75.04%, respectively, indicating that the antioxidant bio-based degradable packaging film has a good antioxidant effect and is more suitable for high-fat food.

[0067] Table 1

[0068]

[0069] (7) Determination of the response effect of volatile ammonia: Taking Example 1 as the object, the response sensitivity of the composite film to volatile ammonia was monitored using a smart phone at room temperature. The results are shown in the attached figure. Figure 7 Under natural light, the composite film was observed to change from bright yellow to yellow-brown, and under an excitation wavelength of 365nm, the composite film fluorescence color was observed to change from light yellow to colorless. This is because quercetin nanocrystals react with ammonia vapor and undergo deprotonation, indicating that the antioxidant bio-based degradable packaging film can sense changes in environmental pH and display them through colorimetric-fluorescence dual modes.

[0070] (8) Degradation performance measurement: The degradability of the examples was measured using the soil burial method. The results are as follows: Figure 8 As shown in the figure, due to the activities of fungi and other microorganisms in the soil, the examples were almost completely degraded within the 28 days of observation, while the polyethylene film (PE) used as the control had an intact structure and was not degraded during the observation period, indicating the degradable properties of the examples.

[0071] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and equivalent scope, the present invention is not limited to the specific details and the illustrations shown and described here.

Claims

1. A method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film, characterized in that: The method comprises the following preparation steps: (1) dissolving quercetin in anhydrous ethanol to obtain a quercetin-ethanol solution; (2) adding the quercetin-ethanol solution dropwise into supercooled water with a volume 9 times that of the quercetin-ethanol solution, and simultaneously performing ultrasonic treatment to obtain a quercetin suspension solution; (3) Mix wheat gluten and deionized water, perform ultrasonic treatment, adjust the solution pH to 8 with 5 wt % sodium hydroxide aqueous solution, add trypsin, perform enzymolysis at 30-50 ° C for 3 h, and then inactivate the enzyme at 95 ° C for 10 min. Centrifuge at a speed of 10,000 rpm for 8-20 min, take the supernatant, and dry at -48 ° C for 20 h to obtain intermediate A; (4) Mix the intermediate A with deionized water, adjust the solution pH to 11 with 5 wt % sodium hydroxide aqueous solution, add the quercetin suspension solution and chitosan solution in sequence while stirring at 20-60 rpm, adjust the solution pH to 6 with dilute hydrochloric acid, stir at 200 rpm for 3-10 min, and then perform ultrasonic treatment to obtain a coating suspension solution; (5) dissolving polyvinyl alcohol powder in deionized water at a dissolution temperature of 85-90°C for 2-4 hours to obtain a polyvinyl alcohol solution having a concentration of 2-5 wt%; The chitosan solution and the polyvinyl alcohol solution are mixed evenly, glycerol and the coating suspension solution are added, and then poured into a mold, cast, and dried at 40-60°C for 3-5 hours to obtain a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film with a thickness of 0.01-0.03 mm.

2. The method for preparing a quercetin nanocrystal-enhanced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The concentration of the quercetin-ethanol solution in step (1) is 10-30 mg / mL.

3. The method for preparing a quercetin nanocrystal-enhanced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The ultrasonic parameters of step (2) are: frequency of 21 kHz and time of 10 to 20 min.

4. The method for preparing a quercetin nanocrystal-enhanced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The concentration of the quercetin suspension solution in step (2) is 1-3 mg / mL.

5. The method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The ultrasonic parameters of step (3) are as follows: temperature of 40-70°C, frequency of 60 Hz, and time of 10-30 min.

6. The method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: In step (3), the mass ratio of wheat gluten, deionized water and trypsin is 10:90:

4.

7. The method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: In step (4), the mass ratio of the intermediate A, deionized water, quercetin suspension solution, and chitosan solution is 1:20:2:

20.

8. The method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The ultrasonic parameters of step (4) are as follows: frequency of 30-50 kHz, intermittent ratio of 20 / 5 s / s, power of 300 W, and time of 5-13 min.

9. The method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The preparation method of the chitosan solution in step (4) and step (5) is as follows: chitosan powder is dissolved in a 2% (v / v) acetic acid aqueous solution at a dissolution temperature of 50-60° C. for a dissolution time of 2-4 hours to obtain a chitosan solution having a concentration of 1.5-4wt%.

10. The method for preparing a quercetin nanocrystal-reinforced chitosan / polyvinyl alcohol antioxidant bio-based degradable packaging film according to claim 1, characterized in that: The mass ratio of the chitosan solution, polyvinyl alcohol solution, glycerol and the coating suspension solution in step (5) is 10:5~30:0.045:1~3.